APPLICATION OF BLOCKCHAIN BASED WAQF CROWDFUNDING IN FISHERMEN GROUP: CASE STUDY OF NAMBANGAN AND CUMPAT, SURABAYA - Raditya Sukmana; Rahmat Heru Setianto; Gancar Candra Premananto; Shochrul Rohmatul Ajija (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: The image of fishermen so far is a group of people classified as poor. One effort to reduce poverty is to revive the microenterprise economy through cooperatives and utilize waqf funds as an alternative source of financing for microbusinesses. The Mining and Cumpat Fishermen Group of Kenjeran District in Surabaya City has now received capital injections from productive endowments in their cooperatives. However, another problem arises from productive waqf there, the waqf that is collected is not as much as what is needed by the person. Purpose: This service program is expected to produce an outcome that is a blockchain based application that can facilitate endowments and willingness. Thus it is expected to help increase the capital of the Fishermen and Cumpat Fishermen Group, Kenjeran District, Surabaya City. Method: This service program used a participatory method whereby the companion was also involved in the application business process. In addition, the companion also asked for active participation from the mauquf alaih to provide detailed information about his business. Thus, the facilitators could promote to the prospective waqf to channel the endowment funds. Results: This assistance program produced a waqf application with blockchain technology that can be accessed on waqf.network. Conclusion: This program was considered effective in growing trust in the distribution of waqf funds. In addition, maukuf alaih also makes it easier to get investors in developing their businesses.